Revenue patterns of piped water services in rural Africa - Armstrong, AM (2022)
Rural Africa lags behind all other global regions in progress towards establishing universal and equitable access to safely managed drinking water. This challenge is marked by a notional interest in piped water for achieving service level goals while increasing demand and financial viability. Yet, a paucity of reliable information and evidence perpetuates unrealistic assumptions of how infrastructure and payment collection alternatives influence seasonal revenue generation. The emergence of professional service delivery models offers new sources of operational and financial data with potential to address knowledge gaps and inform viable, resilient, and equitable drinking water investments.